Byronic Hero in the Main Character of Elizabeth Cody Kimmel’s ParaNorman Novel - Zahratin Nor; Anjar Dwi Astuti; Nita Maya Valiantien (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This research discussed the main character in ParaNorman novel that has Byronic hero characteristics and also about the hero’s journey. This research used theories from Peter Thorslev and Atara Stein for the Byronic hero characteristics and Evie Lotze for the stages of hero's journey. The objective of this research is to find out the Byronic hero characteristics and the stages of hero’s journey portrayed through the main character named Norman Babcock. The result of this analysis shows Norman has several characteristics which included anti-social, superhuman-abilities, tender with girls, rebel, restless wandering, responsible and mysterious person. The result also showed that the journey Norman had in ParaNorman followed the stages of all the four stages of hero’s journey such as the call, wandering, help from unlikely places and others, and the last triumph or returning with the boon. Therefore, by analyzing characteristics and the stages of the hero’s journey by using theories from Peter Thorslev, Atara Stein, and Evie Lotze this research had concluded that Norman was able to fulfill the stages of the hero journey as a Byronic hero character in ParaNorman novel.